THE CORRELATION AMONG KNOWLEDGE OF OCCUPATIONAL SAFETY AND HEALTH (OSH), SAFETY AWARENESS AND UNSAFE ACTION ON NURSES IN HOSPITAL - Ruwanto, Zata Sabrina; Widjanari, Maria Paskanita; Reni Wijayanti (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Unsafe work behavior, such as not wearing PPE, not following work procedures and work safety regulations, and not working carefully is an action that caused 88% of work accidents. The rate of occurrence of minor work accidents in hospitals is 20% higher than workers in other industries. Purpose: To prove that there was a correlation between knowledge of OSH as well as safety awareness and unsafe action on nurses in Hospital X. Method: This study used an observational analytic method with a cross-sectional approach. The research sample was 88 respondents, and it was taken by using the total sampling technique. The research instrument used was a valid and reliable questionnaire. Data analysis used Somer's d test for bivariate data processing and the Ordinal Logistics Regression test. Result: The results of the Somer's d test for correlation between the knowledge of OSH and unsafe action resulted in p-value 0.00, while the results of the Somer's d test for correlation between safety awareness and unsafe action resulted in p-value 0.000. Furthermore, the Ordinal Logistics Regression test that was carried out with the independent variable in the study that had a greater effect on unsafe action was safety awareness with a wald value of 15.001. The results of the Nagelkerke R-square were 0.482 (48.2%), hence the independent variables could explain the dependent variable by 48.2%. Conclusion: The result of this study showed that there was a significant correlation between the knowledge of occupational health and safety awareness with unsafe action.